CCAFS impact assessment of national policy engagement in Kenya on uptake of climate-smart agriculture technologies and practices - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
In other countries in EA where CCAFS has been active in supporting policy processes. These include